Influência do desgaste das garras e pressão de inflação de pneus na vibração transmitida ao operador de trator agrícola - Uchôa, Mayara Rodrigues (2021)
Agricultural operations carried out constantly in the field subject operators to levels of whole body vibration that can have harmful health effects. Considering that one of the factors that interfere in the vibration intensity is the tires fitted to the a gricultural tractor, the objective of this work was to evaluate the levels of vibration incident on the entire body of an agricultural tractor operator under the influence of two types of tires: new and with worn claws, using three inflation pressures, the se variables being analyzed at three speeds. The experiment was carried out in accordance with the guidelines of the NHO 09 and NBR ISO 5008 standards. The experiment was conducted in the experimental area of the Laboratory for Investigation of Acciden ts with Agricultural Machines (LIMA), belonging to UFC, in Fortaleza/CE. A 120 hp BM 120 4x2 TDA tractor was used, equipped with 14.9 24 R 1 tires on the front axle and 18.4 34 R 1 on the rear axle. The working speed was set at 1860 rpm for three speeds: V 1 4,2 km h 1 , V2 6 ,2 km h 1 and V3 8 ,6 km h 1 . The 2x3 Fully Casual Design was used, with two sets of tires, worn diagonals (PD) and new diagonals (PN) and three inflation pressures P1, P2 and P3 corresponding to 96,5, 110,3 e 124,1 kpa for the front tires and 110,3, 124,1 e 137,9 kpa for the hindquarters, with 5 repetitions and duration of travel of 3 minutes for each evaluation. The acquisition of vibration data was performed with a triaxial accelerometer, attached to the seat and a vibration meter. The following vibration parameters were evaluated: Average acceleration, maximum peak, acceleration resulting from normalized exposure (aren); and Resultant Vibration Dose Value (VDVR). The determination of the wear of the claws was made using a digital c aliper, affixed to a wooden support. For statistical analysis of the data, the ASSISTAT version 7.7 beta program was used, normality was verified, they were submitted to analysis of variance by the F test, and when significant, the means were compared by t he Tukey test, at 5% significance. It is concluded that the treatments with new tire in combination with the lowest inflation pressures, presented lower whole body vibration indexes. In addition, all treatments presented VDVR values and are below the exp osure limit, except for treatments with worn tires at a speed of 8 ,6 km h 1 , which does not characterize these working conditions as unhealthy.